Transfer of mesenchymal stem cells and cyclosporine A on alkali-injured rabbit cornea using nanofiber scaffolds strongly reduces corneal neovascularization and scar formation - Cejka, Cestmir; Cejkova, Jitka; Trosan, Peter; Zajicova, Alena; Sykova, Eva; Holan, Vladimir (Histology and histopathology, 2016)
The aim of this study was to examine whether nanofiber scaffolds seeded with rabbit bone marrow mesenchymal stem cells (MSCs nanofibers) transferred onto the damaged corneal surface and covered with cyclosporine A (CsA)-loaded nanofiber scaffolds (CsA nanofibers) enable healing of the rabbit cornea injured with 1N NaOH. The healing of damaged corneas was examined morphologically, immunohistochemically and biochemically on day 24 after the injury. Compared to untreated injured corneas, where corneal ulceration or large corneal thinning or even perforation were developed, injured corneas treated with drug free nanofibers healed without profound disturbances in a majority of cases, although with fibrosis and scar formation. In injured corneas treated with CsA nanofibers or MSCs nanofibers, the development of scar formation was reduced. Best healing results were obtained with a combination of MSCs and CsA nanofibers (MSCs-CsA nanofibers). Corneas healed with highly restored transparency. Neovascularization highly expressed in untreated injured corneas and reduced in corneas treated with CsA nanofibers or MSCs nanofibers, was suppressed in corneas treated with MSCs-CsA nanofibers. The levels of matrix metalloproteinase 9, inducible nitric oxide synthase, interleukin 6, α-smooth muscle actin, tumor growth factor β and vascular endothelial growth factor were significantly decreased in these corneas as compared to untreated corneas, where the levels of the above mentioned markers were high. In conclusion, MSCs-CsA nanofibers were effective in the treatment of severe alkali-induced corneal injury.
Keywords: modely nemocí na zvířatech; jizva; Corneal Neovascularization; kaustika; Immunosuppressive Agents; Sodium Hydroxide; Mesenchymal Stem Cell Transplantation; Corneal Injuries; Drug Carriers; králíci; Caustics; neovaskularizace rohovky; Drug Delivery Systems; Animals; nanovlákna; ženské pohlaví; Wound Healing; zvířata; Cyclosporine; Disease Models, Animal; Rabbits; Nanofibers; Tissue Scaffolds; cyklosporin; poranění rohovky; tkáňové podpůrné struktury; hydroxid sodný; Female; nosiče léků; transplantace mezenchymálních kmenových buněk; lékové transportní systémy; imunosupresiva; hojení ran; Cicatrix